The effects of dietary glutamine, glycine, and sodium chloride concentration on nursery pig growth performance - Groesbeck, C.N.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
We conducted a trial to evaluate the effects of feeding added salt (0.38% in addition to the 0.35% already added to the diet) and a 0.70% addition of a blend of 50% glutamine and 50% glycine to weanling pigs as a substitute for spray-dried animal plasma. A total of 216 pigs (initial BW 12.4 ± 1.9 lb and 21 ± 2 d of age) were used, with six pigs per pen and six pens per treatment. Pigs were randomly allotted to pens, blocked by weight, and assigned to one of the six dietary treatments. The six treatments were a negative control diet based on corn-soybean meal, a positive contol diet containing 5% spray-dried animal plasma, and diets with high concentrations of synthetic amino acids. Diets were arranged in a 2 × 2 factorial, with or without 0.7% of a 50:50 blend of glutamine and glycine and with or without added salt (0.38% more than the basal level of 0.35% in all diets). From d 0 to 7, ADG and ADFI increased (P<0.05) for the pigs fed the positive with all other treatments. Pigs fed the synthetic amino acid diets (glutamine:glycine and Na treatments) had improved (P<0.05) F/G, compared with that of pigs fed the negative and positive control diets. From d 7 to 14, pigs fed the positive control diet had increased ADG, compared with that of the pigs fed the negative control, but ADG did not differ from that of pigs on any of the four glutamine: glycine and Na treatment diets. Pigs fed the positive control diet had greater ADFI and improved F/G for d 7 to 14, compared with those of pigs in all other treatments. For the overall feeding period, (d 0 to 14), pigs fed the positive control diet had a numerical improvement in ADG, compared with that of pigs fed the synthetic amino acid diets. Pigs fed the positive control diet also had a greater (P<0.05) ADG and ADFI than those fed the negative control diet. The pigs fed the positive control diet consistently had greater ADFI than pigs in all other treatments. The increase in ADFI corresponds to the increase in ADG for the overall feeding period. The data suggest that adding spray-dried animal plasma to the diet improves ADFI and ADG, and it seems that synthetic amino acid diets containing added Na and a 0.70% dietary blend of 50:50 glutamine:glycine can not equal the response exhibited when spray-dried animal plasma is added to nursery pig diets. Pigs fed the synthetic amino acid diets did have greater growth performance than that of pigs fed the negative control diet. The addition of large amounts of salt or the glutamine:glycine blend to synthetic amino acid diets did not have any influence on pig performance in this experiment.
Swine research, 2005 is known as Swine day, 2005
Keywords: Nursery pig; Glutamine; Glycine; Sodium; Swine